The participation of women in the public sector: The case of Lao Cai province, Vietnam - Nguyen, Thi Tu (Trung tâm Đào tạo và Giáo dục quốc tế, 2017)
Biological differences between male and female are unchangeable. Characteristics that are interchageable between male and female are reagarded as gender factor. For example, women may also be strong and assertive.